2013
DOI: 10.1524/zpch.2013.0407
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Reactive and Inelastic Scattering: Differential Cross Section of the H + HD → HD(v′, j′) + H Reaction

Abstract: The H + HD → HD(ν , j ) + H reaction has been studied experimentally and theoretically. Differential cross sections of HD(ν , j ) products have been measured by means of a Photoloc technique and calculated using a time-independent quantum mechanical theory. Three product states: HD(ν = 1, j = 8) at a collision energy (E coll ) of 1.97 eV; HD(ν = 2, j = 3) at E coll = 1.46 eV; and HD(ν = 2, j = 5) at E coll = 1.44 eV, show very good agreement between theory and experiment. The other two, highly rotationally exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…GP effects in molecular spectra have been reported in several theoretical treatments [4,12,[28][29][30][31][32][33][34][35][36][37][38] and it has been confirmed experimentally for the molecules Cu 3 , [39] Li 3 , [40] and Na 3 [41]. In stark contrast, the experimental measurement of a GP effect in molecular scattering has continued to be elusive to this day [42,43]. The first theoretical prediction of a GP effect in scattering was made by Mead for the H + H 2 system [44].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…GP effects in molecular spectra have been reported in several theoretical treatments [4,12,[28][29][30][31][32][33][34][35][36][37][38] and it has been confirmed experimentally for the molecules Cu 3 , [39] Li 3 , [40] and Na 3 [41]. In stark contrast, the experimental measurement of a GP effect in molecular scattering has continued to be elusive to this day [42,43]. The first theoretical prediction of a GP effect in scattering was made by Mead for the H + H 2 system [44].…”
Section: Introductionmentioning
confidence: 94%
“…At energies above the conical intersection, large GP effects on the DCSs were reported which give rise to broader bimodal features [61][62][63]. Unfortunately, a recent experimental effort was unable to resolve the GP oscillations in the DCSs for the H + HD  H + HD reaction at energies below the conical intersection [42,43]. No significant GP effects have been reported in the integral cross sections (or reaction rate coefficients) at any thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in the present study is the role of the geometric phase (GP) associated with the D 3 h conical intersection (CI) in H 3 . For thermal scattering at total energies below 1.8 eV, many partial waves contribute and the GP effects all but wash-out in the partial wave sum for both the integral and differential cross sections. , However, for thermal scattering at higher total energies above 1.8 eV but below the energy of the CI (∼2.7 eV), some small GP effects were finally reported in the differential cross sections (DCSs) by Juanes-Marcos and Althorpe . Additional theoretical studies at energies above the CI reported large GP effects, which lead to bimodal features in the DCSs. An experimental attempt to resolve the theoretically reported GP induced oscillations in the DCSs for the H + HD → H + HD reaction at energies below the CI was unsuccessful. , However, a recent high-resolution experiment finally measured the GP effect for the first time in the DCSs for the H + HD → H 2 + D reaction at a collision energy of 2.77 eV (total energy 2.99 eV) . Interference effects due to the GP give rise to a peak at zero scattering angle (forward scattering).…”
Section: Introductionmentioning
confidence: 99%
“…A least-squares fitting procedure , was performed to compare the theoretical calculations with experimental measurements. The fitting parameter R 2 value is used to quantify the quality of the fitting process and to provide a measure of how well the theoretical DCSs agree with the experimental ones. A value of R 2 = 1 represents a perfect agreement.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretically calculated DCSs have been modified to simulate the experimental conditions as described above in Slow-Channel Correction (see Figure ) and presented in Figure using solid black lines. A least-squares fitting procedure , was performed to compare the theoretical calculations with experimental measurements. The fitting parameter R 2 value is used to quantify the quality of the fitting process and to provide a measure of how well the theoretical DCSs agree with the experimental ones.…”
Section: Resultsmentioning
confidence: 99%